Home production, market production and the gender wage gap incentives and expectations - Albanesi, Stefania; Olivetti, Claudia (Working paper series / National Bureau of Economic Research, 2006)
The purpose of this paper is to study the joint determination of gender differentials in labor market outcomes and in the household division of labor. Specifically, we explore the hypothesis that incentive problems in the labor market amplify differences in earnings due to gender differentials in home hours. In turn, earnings differentials reinforce the division of labor within the household, leading to a potentially self-fulfilling feedback mechanism. The workings of the labor market are key in our story. The main assumptions are that the utility cost of work effort is increasing in home hours, and that higher effort should correspond to higher incentive pay. Household decisions are Pareto efficient, leading to a negative correlation between relative home hours and earnings across spouses. We use the Census and the PSID to study these predictions and find that they are supported by the data.